2019
DOI: 10.1093/jcr/ucz044
|View full text |Cite
|
Sign up to set email alerts
|

The Impostor Syndrome from Luxury Consumption

Abstract: The present research proposes that luxury consumption can be a double-edged sword: while luxury consumption yields status benefits, it can also make consumers feel inauthentic, producing what we call the impostor syndrome from luxury consumption. As a result, paradoxically, luxury consumption may backfire and lead consumers to behave less confidently due to their undermined feelings of self-authenticity. Feelings of inauthenticity from luxury consumption may arise because consumers perceive luxury as an undue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 67 publications
5
54
1
Order By: Relevance
“…Despite certain benefits associated with luxury consumption, such as attribution of status, preferential treatment, and affiliation with desirable social groups and mates (Bellezza and Berger 2020;Griskevicius et al 2007;Veblen 1899), recent work documents many social costs associated with the consumption of high-end, expensive products. For example, consumers who own luxury goods are considered less warm and authentic and more driven by impression-management motives than consumers who do not own them (Cannon and Rucker 2019;Ferraro, Kirmani, and Matherly 2013;Garcia, Weaver, and Chen 2018;Goor et al 2020). These negative perceptions may also be driven by a failure to consider the durability of high-end products at the observers' end.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Despite certain benefits associated with luxury consumption, such as attribution of status, preferential treatment, and affiliation with desirable social groups and mates (Bellezza and Berger 2020;Griskevicius et al 2007;Veblen 1899), recent work documents many social costs associated with the consumption of high-end, expensive products. For example, consumers who own luxury goods are considered less warm and authentic and more driven by impression-management motives than consumers who do not own them (Cannon and Rucker 2019;Ferraro, Kirmani, and Matherly 2013;Garcia, Weaver, and Chen 2018;Goor et al 2020). These negative perceptions may also be driven by a failure to consider the durability of high-end products at the observers' end.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…as an incident factor in purchasing luxury (Dhaliwal et al, 2020). Therefore, several psychological variables have been investigated to explain the motivations for luxury consumption, such as propensity to materialism (Mainolfi, 2019;Sun et al, 2014;Wong & Ahuvia, 1998), self-concept (Gil et al, 2012;Nyadzayo et al, 2020;Truong & McColl, 2011), attitudes towards luxury consumption (Dubois et al, 2005;Jhamb et al, 2020;Schade et al, 2016), personality traits (Kastanakis & Balabanis, 2012van Schalkwyk, 2014) and self-authenticity (Goor et al, 2020;Morhart & Malär, 2020).…”
Section: Consumers' Psychological Characteristics Have Been Recognizedmentioning
confidence: 99%
“…They suggested that power can affect the psychological utility which can affect spending behavior of consumers. However, Goor et al (2019) showed that luxury consumption may lead consumers to behave less confidently due to their undermined feelings of self-authenticity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Threatened individuals want to purchase status goods to ease their psychological pain when alternate affirmative resources are not available. Status goods provide individuals with important psychological support to protect their self-integrity against negative psychological situations (Sivanathan & Pettit 2010).On the other hand, according to Goor et al (2019), nonluxury products are less likely to make individuals feel inauthentic because they are not accepted as products providing a privilege. Pino et al (2019) approached the issue of purchasing luxury products from a different perspective, and they investigated the effects of brand prominence and status consumption on consumers' willingness to buy luxury goods across emerging and mature markets in India and the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation